"… a few patches of potato-ground and rude dwelling places": views of New Zealand through Lockean eyes - Schmidt, Tyson (Architectural History Aotearoa, 2012)
One of the first pieces of legislation passed by the newly formed General Assembly of New Zealand was the Waste Lands Act 1854, providing for the sale, letting, disposal and occupation of lands acquired by the Crown from Māori. The waste lands concept was an early part of the colonial project, but gained particular traction with the demise of the New Zealand Company in the early 1850s, Governor Grey's departure in 1853, and settler-dominance of the First Parliament in the mid 1850s. The origin of the concept stems from Enlightenment philosopher John Locke, whose labour theory of property held that a right to property arose through exertion of labour on that land – or put the other way, uncultivated or unoccupied meant un-owned. Adopted by the likes of Edward Gibbon Wakefield, the waste lands concept underpinned a strongly economic approach to settlement. It has already been well established how images of New Zealand's landscape and built environment were used to support settlement efforts – depictions of emptiness served to "stimulate avarice for land in the heart of a potential settler who has none" (as Hamish Keith puts it). We can extend such analyses by reading these images in light of the waste lands concept, showing how this reflected relationships between the Crown and Māori during the 1850s.